2011
DOI: 10.1111/j.2041-210x.2011.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating abundance from presence/absence maps

Abstract: Summary1. An important question in macroecology is: Can we estimate a species' abundance from its occurrence on landscape? Answers to this question are useful for estimating population size from more easily acquired distribution data and for understanding the macroecological occupancy-abundance relationship. 2. Several methods have recently been developed to address this question, but no method is general enough to provide a common solution to all species because of the wide variation in spatial distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…This approximate AIC balances the goodness of fit (as measured by the log-likelihood of the regression relating observed and fitted values) and the number of parameters of the models (38). Because the nonlinear model (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…This approximate AIC balances the goodness of fit (as measured by the log-likelihood of the regression relating observed and fitted values) and the number of parameters of the models (38). Because the nonlinear model (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…In conservation, occupancy is typically regarded as inferior to abundance because it does not provide early warning of population declines (Pollock 2006;Joseph et al 2006). However, by assuming that a species' detectability is largely a function of its abundance, and recognizing that change in population size typically accompanies change in proportion of area occupied Longcore et al 2010), it is possible to reliably estimate abundance and population trend from occupancy data (He and Gaston 2000;Royle and Nichols 2003;Pollock 2006;Zhou and Griffiths 2007;Hui et al 2009;Hwang and He 2011;but see Strayer 1999). Detection/non-detection data tend to approximate patch-level processes with far less effort than abundance surveys (MacKenzie et al 2003;Zhou and Griffiths 2007), and may provide the best information under limited resources.…”
Section: Introductionmentioning
confidence: 99%
“…When applied to forest census data (Condit et al, 1996), they showed that the estimator based on the generalized gamma Poisson model could improve estimation of abundance from occurrence data. To date, however, no statistical properties of the estimators of He and Gaston (2000) and Hwang and He (2011) are known. Even consistency has not been proven.…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%
“…It is more appropriate to consider the spatial correlation of the λ ij over the cells so that the λ ij in neighboring cells are more similar than between those that are further apart. This observation motivated Hwang and He (2011) to model the mean levels as a gamma random field. Formally, let V st , s, t ∈ Z Z = {0, −1, 1, −2, 2, .…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation